AVALIAÇÃO DA COMPOSIÇÃO QUÍMICA E APLICAÇÃO BIOLÓGICA DO ÓLEO ESSENCIAL DA Lantana aff. Lilacina Desf. (MILHO DE GRILO),UMA Verbenaceae - MACIEL, Luênery Henrique de Oliveira,; ADÃO, Cintia Cristina Domiciano,; SCHOT, Joice de Oliveira,; SILVA, Rogério César de Lara, (ANAIS DO ENIC, 2022)
-